PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN TALAOK BAYANG - Reflina, Reflina; Anggraini, Villia; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTThe research was conducted based on the fact which indicated the students low motivation to rehearse the learning material which emerged the students difficulties to do the mathematical questions. The purpose of this research was to know whether the students treated by college ball strategy have better comprehension of mathematical concept than those who are treated by conventional strategy. This was an experimental research which used random sampling. The population was the VIII grade students of MTSN Talaok Bayang. The VIII.5 was the experimental class while the VIII.3 class was the control class. The instrument was final test. The hypotheses was tested by one tailed test. It was found that t-obtained > t-table. Thus,it can be concluded that the students treated by college ball strategy had better mathematical comprehension than those who treated the conventional strategy.